If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y = -0.5(x + -8)(x + -32) Reorder the terms: Y = -0.5(-8 + x)(x + -32) Reorder the terms: Y = -0.5(-8 + x)(-32 + x) Multiply (-8 + x) * (-32 + x) Y = -0.5(-8(-32 + x) + x(-32 + x)) Y = -0.5((-32 * -8 + x * -8) + x(-32 + x)) Y = -0.5((256 + -8x) + x(-32 + x)) Y = -0.5(256 + -8x + (-32 * x + x * x)) Y = -0.5(256 + -8x + (-32x + x2)) Combine like terms: -8x + -32x = -40x Y = -0.5(256 + -40x + x2) Y = (256 * -0.5 + -40x * -0.5 + x2 * -0.5) Y = (-128 + 20x + -0.5x2) Solving Y = -128 + 20x + -0.5x2 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Simplifying Y = -128 + 20x + -0.5x2
| -5x+6y=-30 | | 3=2(4-5x) | | 20=6n+2 | | 2x^2-6x-18=0 | | x+(4x-33)=180 | | 2x+6=3-10x | | -16t^2+35t-18=0 | | -7-2x=-1 | | -2-x=3 | | x-(x*.3)=2500 | | 4=3-x | | 5+2*4-10=3 | | 8x-10=3+3x | | -6x+7=-49 | | 5x+7=6-2x | | -6x-7=-47 | | -4-x=2 | | 6-3x=-2 | | -4=-1-x | | 4*x^2-4= | | 6+(-5)-4+1= | | x+2*4x-8= | | 9-4x=-7 | | (x-4)(x-3)=8 | | 4x^2+7=9 | | 2X+3Y=132 | | 4a+13=33 | | -20x^2-7x+3=0 | | 17x-5=12x+6 | | 4x-12y=24 | | 3z-4=5z-2 | | 15x^2=25x |